تيجان ستانلس ستيل المغطاة مقابِل غير المغطاة: دراسة سريرية عشوائية - رسلان نبيه; نور الله عبد الوهاب; معروف هبه (Latakia University Journal -Medical Sciences Series, 2014)
الهدف: تقييم ديمومة تغطية تيجان الستانلس ستيل للأرحاء اللبنية بالنانو كومبوزيت كتقنية خارجية ضمن عيادة طبيب الأسنان ومقارنتها مع تيجان الستانلس ستيل التقليدية وتقييم رضى الأهل عن هذه التيجان. المواد والطرق: شملت عينة الدراسة 32 تاج ستانلس ستيل: 16 تاجاً تقليدياً و16 تاجاً تمت تغطيتها بالنانو كومبوزيت (Tetric EvoCeram®) باستخدام نظام اصلاح الخزف ( Ceramic Repair ,Intro Pack, Ivoclar Vivadent) ولدى 10 مرضى. تلقى كل مريض وبشكل عشوائي نوعي التيجان كليهما على 2 أو 4 أرحاء سفلية متناظرة وقد استخدم في هذه الدراسة تصميم الفم المقسوم. تم إجراء التقييم السريري والشعاعي للتيجان بعد 6,3,1 أشهر وقد قيمت المتغيرات التالية: مشعر الصحة الفموية المبسط ومشعر اللثة وامتداد الحواف وانطباق الحواف السريري والشعاعي ومناطق التماس والعظم السنخي بين السني وتقشر الوجه التجميلي كما تم تقييم رضى الأهل باستخدام مقياس نموذج Likert. النتائج: كل التيجان كانت موجودة بعد 6 أشهر. لم يلاحظ فقدان الكومبوزيت بالكامل من أي من التيجان المغطاة، تراوحت درجات سلامة الوجوه بين (1= لا تقشر في الوجه التجميلي ، 2= تقشر< 2 ملم ، 3 = تقشر> 2 ملم على سطح واحد ، 4 = تقشر > 2 ملم على سطحين). كانت الوجوه سليمة بنسبة 50%(8) بعد 3 أشهر وانخفضت هذه النسبة إلى 37.5%(6) بعد ستة أشهر وبقيت النسبة المئوية للدرجتين 2 و3 من التقشر ثابتة 31.25%(5) بعد 3 و6 أشهر بينما ازدادت النسبة المئوية للوجوه ذات التقشر الأكثر من 2 ملم على سطحين من 18.75%(3) بعد 3 أشهر إلى 31.25%(5) بعد 6 أشهر. ولم يلاحظ أية اختلافات مهمة إحصائياً بين التيجان التقليدية والتجميلية بالنسبة لكل المتغيرات المدروسة، كانت الصحة الفموية مرتبطة بشكل هام إحصائياً مع التهاب اللثة في جميع المتابعات بينما كان لدرجة انطباق الحواف شعاعياً ارتباط مهم احصائياً مع التهاب اللثة في المتابعة الثالثة فقط 0.034P=. كان رضى الأهل الكلي عن تيجان الستانلس ستيل ذات الوجه التجميلي عالياً. الاستنتاج: إن إجراء تغطية تيجان الستانلس ستيل الخلفية بالنانو كومبوزيت يمكن أن يكون تقنية جيدة لتحسين النواحي التجميلية لتيجان الستانلس ستيل مع معدل رضى مرتفع للأهل ودون أية آثار ضارة على النسيج اللثوي. Purpose: The purpose is to assess chairside veneering posterior stainless steel crowns with nanocomposite and to compare them with conventional stainless steel crowns as well as to evaluate parental acceptance of these esthetic crowns. Material and methods: The study included 32 crowns (16 conventional and 16 esthetics that were chairside veneered with nanocomposite, Tetric Evoceram®, using Ceramic Repair ,Intro Pack, Evoclar Vivadent). The crowns were placed in 10 children. A split mouth design was used. Each participant randomly received each crown type on 2 or 4 pair matched lower molars. The crowns were evaluated after 1,3,6 months and the following parameters were assessed: oral hygiene index, Gingival index, crown marginal extension, crown marginal adaptation clinically and radiographically, proximal contact areas, interproximal bone level and facing fracture. A Likert Type Scale was used to determine parental satisfaction. Results: All crowns were retained after 6 months. Non of the esthetic crowns had a complete face lost. The integrity of the facing was rated from 1-4 (1= no fracture, 2=less than 2 mm, 3= more than 2 mm in one surface, 4= more than 2 mm in 2 surfaces). Facing was intact in 50% (8) of the crowns after 3 months and in 37.5% (6) after 6 months. Facing fractures were rated 2, 3 in 31.25% (5) of the crowns at both 3 and 6 months, and were rated 4 in 18.75% (3) at 3 months and in 31.25% (5) at 6 months. No difference was found between the result of Gingival index, proximal contacts, crown marginal extension and crown marginal adaptation clinically and radiographically for both esthetic and conventional crowns in all recalls. Oral hygiene level had a significant effect on the gingival index after 1,3,6 months and radiographic crown marginal adaptation had a significant effect on gingival index only after 6 months p=0.034. The overall parental satisfaction with the esthetic crowns was high. Conclusions: chairside vereering stainless steel crowns with nanocomposite can be a good way to improve the esthetics of SSC with high parental satisfaction, and with out adverse effects on gingival tissue.